Marine-derived new peptaibols with antibacterial activities by targeting bacterial membrane phospholipids - Chen, Shang; Liu, Dong; Wang, Liyang; Fan, Aili; Wu, Mengyue; Xu, Ning; Zhu, Kui; Lin, Wenhan (Acta pharmaceutica Sinica. B, 2025)
Antibiotic resistance is spreading at a faster rate than new antibiotic agents applied for clinical remedies. It is an urgent need to discover potential compounds to combat multidrug-resistant (MDR) bacteria. Marine fungi offer a promising avenue for mining antibiotic-like molecules with chemical diversity. To discover structurally novel and antibiotic metabolites, we screened the in-house marine fungus genome library and found a fungus Stephanonectria keithii LZD-10-1 containing a non-ribosomal peptide synthetase (NRPS) cluster with 18 modules to synthesize a new subfamily of peptaibols with effective eradication against MDR pathogens. Targeting isolation of the cultured fungus afforded six new peptaibols, which exhibit the ability to kill MDR bacteria by targeting bacterial membrane phospholipids, especially phosphatidylglycerol (PG), leading to the dysfunction of bacterial membranes. Furthermore, their efficacies against methicillin-resistant Staphylococcus aureus (MRSA) in both Galleria mellonella and mouse wound infection models were observed. This study underscores the significance of employing genome-guided approaches to identify untapped marine fungi as potential sources for novel antibiotic candidates with unique scaffolds. SK-Ps, a new subfamily of peptaibol isolated from a deep-sea fungus, effectively killed multidrug-resistant bacteria by targeting bacterial membrane phospholipids, leading to bacterial membrane dysfunction, abnormal division, and ultimately death. [Display omitted]